"2 for 1 Phenomenon" on Implantable Cardioverter Defibrillator Intracardiac Tracing. Issue 12 (23rd July 2016) - McCLENDON, ERIC; SUZUKI, TAKEKI; TANAWUTTIWAT, TANYANAN; RHODES, TROY E.; BERGER, RONALD D.
Abstract : "2 for 1 phenomenon" is simultaneous anterograde conduction over the fast and slow pathways of the atrioventricular (AV) nodal pathway, leading to a double ventricular response from each atrial beat. This phenomenon can initiate AV nodal reentrant tachycardia (AVNRT). The unique induction of AVNRT was observed in a patient with an implantable cardioverter defibrillator in our case. Minimal to no retrograde invasion of the slow pathway from the anterogradely conducted fast pathway depolarization is the most accepted explanation.